2017
DOI: 10.1002/jcph.1028
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapies: Immunologic Effects and Potential Applications Outside of Cancer

Abstract: Two pharmacologic approaches that are currently at the forefront of treating advanced cancer are those that center on disrupting critical growth/survival signaling pathways within tumor cells (commonly referred to as "targeted therapies") and those that center on enhancing the capacity of a patient's immune system to mount an antitumor response (immunotherapy). Maximizing responses to both of these approaches requires an understanding of the oncogenic events present in a given patient's tumor and the nature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 211 publications
(446 reference statements)
0
22
0
Order By: Relevance
“…At the same time, stromal immune cells contribute to a variety of diseases ranging from diabetes to artherosclerosis, fibrosis, cancer and neurodegeneration (Wynn et al, 2013 ). While targeting stromal immune cells is a promising strategy for the development of novel therapeutics for a wide range of diseases (Kersh et al, 2018 ) and recently has gained wide attention in cancer drug discovery and for the therapy of neurological diseases (Villoslada et al, 2008 ; Pitt et al, 2016 ; Alsaab et al, 2017 ; Chitnis and Weiner, 2017 ; Kabba et al, 2017 ; Pogge von Strandmann et al, 2017 ), immune cells also modulate therapeutic response to drugs not directly targeting the immune system (Kersh et al, 2018 ). In drug discovery, in vitro modeling of such complex interactions will require multicellular 3D tissue models with organoids currently being at the forefront for disease modeling, drug screening and drug development.…”
Section: The Extracellular Matrix (Ecm) and Other Microenvironmental mentioning
confidence: 99%
“…At the same time, stromal immune cells contribute to a variety of diseases ranging from diabetes to artherosclerosis, fibrosis, cancer and neurodegeneration (Wynn et al, 2013 ). While targeting stromal immune cells is a promising strategy for the development of novel therapeutics for a wide range of diseases (Kersh et al, 2018 ) and recently has gained wide attention in cancer drug discovery and for the therapy of neurological diseases (Villoslada et al, 2008 ; Pitt et al, 2016 ; Alsaab et al, 2017 ; Chitnis and Weiner, 2017 ; Kabba et al, 2017 ; Pogge von Strandmann et al, 2017 ), immune cells also modulate therapeutic response to drugs not directly targeting the immune system (Kersh et al, 2018 ). In drug discovery, in vitro modeling of such complex interactions will require multicellular 3D tissue models with organoids currently being at the forefront for disease modeling, drug screening and drug development.…”
Section: The Extracellular Matrix (Ecm) and Other Microenvironmental mentioning
confidence: 99%
“…Moreover, immune‐related pathways, such as those of IFN‐α and IFN‐β, were reported to be enriched in CDK4/6 inhibitor‐resistant breast cancer cells . In one preclinical study, CDK4/6 inhibitors were reported to promote anti‐tumor immunity, similar to other targeted therapies …”
Section: Mechanisms Of Resistance To Cdk4/6 Inhibitorsmentioning
confidence: 99%
“…89 In one preclinical study, CDK4/6 inhibitors were reported to promote anti-tumor immunity, 103 similar to other targeted therapies. 104 . Mechanistically, CDK4/6 inhibitors reduced the activity of DNA methyltransferase, an E2F target protein which promotes cytotoxic T cell-mediated tumor inhibition.…”
Section: Cell Cycle-nonspecific Mechanismsmentioning
confidence: 99%
“…Targeted therapies include receptor tyrosine kinase inhibitors (TKIs) such as erlotinib, sunitinib, and imatinib or monoclonal antibodies such as trastuzumab. Targeted therapies should not directly cause immunosuppression as part of their mechanism of action, but may have unintended inhibitory effects on antigen presenting cell function, T cell activation [ 67 ] and B cell signaling [ 68 ]. Nevertheless, patients treated with sunitinib or sorafenib develop seroprotection with the influenza vaccine comparable to healthy controls [ 69 ].…”
Section: Implications For Patients With Cancermentioning
confidence: 99%